Croatian Women and COVID-19 Pandemic : The Coronavirus Is Not Gender-Blind - World Bank (World Bank, Washington, DC, 2021)
High risk that gender inequalities will widen during and after the pandemic is gains in women’s and girls’ accumulation of human capital, economic empowerment, and voice and agency, may be reversed if no action is taken. Women labor force participation is concentrated in activities that are more sensitive to the crisis. Women are concentrated in sectors where they are more likely to be exposed to the virus. The Coronavirus disease 2019 (COVID-19) crisis didn’t unravel new discrepancies between men and women, it just shone a brighter light on already-existing gaps and issues, all of which can be corrected in the aftermath of the lockdown. It is recommended to improve availability of care which limits women’s labor force participation, including alternative forms of childcare.